THE EFFECT OF INTERPERSONAL COMMUNICATION AND PROBLEM FOCUSED COPING ON STUDENT STRESS IN COMPLETING THESIS AT UISU (CASE STUDY OF 2021 STUDENTS OF MANAGEMENT STUDY PROGRAM, FEB) - Bebi Davilla Nurwandari; Nur M. Ridha Tarigan; M. Tahir (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this study is to determine the effect of interpersonal communication on student stress, to determine the effect of problem-focused coping on student stress, and to determine the effect of interpersonal communication and problem-focused coping on student stress in completing a thesis at UISU (Case Study of 2021 Students of the Management Study Program, FEB). The population used in this study was 112 students who were completing their thesis. Based on Slovin's calculation, the number of samples to be used in this study was 72 people. The data analysis techniques used in this study were by distributing questionnaires, interviews, document studies, and literature studies. The data analysis techniques used in this study were data quality testing, classical assumption testing, and hypothesis testing. Based on the results of the analysis and hypothesis testing, the results of the study are that Interpersonal Communication has a negative and significant effect on Student stress, Problem Focused Coping has a negative and significant effect on Student stress and Interpersonal Communication and Problem Focused Coping have a significant effect on Student Stress in completing the thesis at UISU (Case Study of Students of the 2021 FEB Management Study Program). The suggestion from this study is that students can better apply good Interpersonal communication in the future, both with family, friends, or supervisors. And also Students should focus more on problem solving and managing tasks rationally by managing time well. And for universities can offer training or workshops on stress management and the use of effective coping for students who are in the process of completing their thesis.